Phonological specificity of vowel contrasts at 18-months - Mani, N; Coleman, J; Plunkett, K (Kingston Press Ltd, 2008)
Previous research has shown that English infants are sensitive to mispronunciations of vowels in familiar words by as early as 15-months of age. These results suggest that not only are infants sensitive to large mispronunciations of the vowels in words, but also sensitive to smaller mispronunciations, involving changes to only one dimension of the vowel. The current study broadens this research by comparing infants' sensitivity to the different types of changes involved in the mispronunciations. These included changes to the backness, height, and roundedness of the vowel. Our results confirm that 18-month-olds are sensitive to small changes to the vowels in familiar words. Our results also indicate a differential sensitivity of vocalic specification, with infants being more sensitive to changes in vowel height and vowel backness than vowel roundedness. Taken together, the results provide clear evidence for specificity of vowels and vocalic features such as vowel height and backness in infants' lexical representations.